The applicability of the Teachers' Inclusive Education Attitude Scale on Chinese preservice physical education teachers - Wei, Qian; Luo, Changxin; Li, Yun (Quality in Sport, 2024)
Purpose: This study aims to translate and culturally adapt the revised The Teachers' Attitudes Towards Inclusion Scale Adjusted (TAISA) into Chinese and to evaluate its reliability and validity among Chinese preservice physical educators. Methodology: The English version of The Teachers' Attitudes Towards Inclusion Scale Adjusted (TAISA) was translated through a rigorous process that included a comprehensive literature review and consultations with subject matter experts. A survey was administered to 500 preservice physical educators in Chongqing. The adapted scale underwent thorough analysis, encompassing demographic frequency analysis, item analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and evaluation of test-retest reliability. Results: The analysis revealed that the Chinese version of The Teacher Attitude toward Inclusive Education Scale for Preservice Physical Educators (TAISA-P) retained the original three-factor structure, comprising positive affect, training and perceived competence, and negative affect. After the removal of four items, the final scale consisted of 17 items, with each dimension containing 5 to 6 items. Factor loadings ranged from 0.442 to 0.705, and the model demonstrated a χ²/df ratio of 1.350, a root mean square error of approximation (RMSEA) of 0.066, a non-normed fit index (NNFI) of 0.825, a comparative fit index (CFI) of 0.946, an incremental fit index (IFI) of 0.948, and a goodness-of-fit index (GFI) of 0.834. The overall internal consistency reliability of TAISA-P was 0.759, with dimension-specific reliabilities of 0.835, 0.790, and 0.779. The test-retest reliability coefficient was 0.743 (P < 0.001). Conclusion: The Teacher Attitude toward Inclusive Education Scale for Preservice Physical Educators (TAISA-P) demonstrates strong reliability and validity, thereby establishing it as a suitable instrument for assessing the attitudes of Chinese preservice physical educators toward inclusive education.